The Destruction of the St. Michael’s Golden-Domed Monastery as Covered by Some Ukrainian Periodicals of the Interwar Period. - Grinchenko, Viktor (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Purpose of the study. To consider and analyse diverse materials about the destruction by the Soviet authorities of the unique architectural complex of Kyiv — the St. Michael’s Golden-Domed Monastery, as published on the pages of some Ukrainian periodicals published in Soviet Ukraine and beyond during the interwar period — mainly in the 1930s.Research methodology. The principles of historicism and objectivity were applied. Descriptive, comparative-historical, and historical-critical methods were used.Scientific novelty. The materials presented in this publication can serve as a certain addition to the coverage of state anti-religious policy in Soviet Ukraine, in the part of it that concerned the closure and destruction of religious buildings, in particular, prominent historical and artistic monuments of world importance.Conclusions. The demolition of the St. Michael’s Golden-Domed Monastery became for the conscious Ukrainian community one of the most resonant acts of vandalism by the Bolshevik government. This attitude can be seen in the Ukrainian-language newspaper periodicals of that time in the ethnic lands that were part of Poland, in particular in the Lviv newspapers. In contrast to their clearly pro-Ukrainian position, the servile position was visible in the periodicals of the Ukrainian SSR, where the destruction of the St. Michael’s Monastery was deprived of a negative context. The corresponding publications in the spirit of Bolshevik guidelines actually promoted the invalidation of the values of national architectural traditions and the significance of monuments of sacral architecture.